A Stability-Indicating RP-HPLC-UV Method for Determination and Chemical Hydrolysis Study of a Novel Naproxen Prodrug - Mohamed H. M. Hamid; Tilal Elsaman (Journal of Chemistry)
A new naproxen amide prodrug was synthesized and spectrally characterized and a simple, precise, and accurate stability-indicating RP-HPLC method was developed and validated for determination and chemical hydrolysis study of the prodrug. Forced degradation studies were conducted as per the International Conference on Harmonization (ICH) guidelines to establish the stability-indicating power of the method. Separations were performed on a C18 column (150 × 4.6 mm i.d., 5 μm p.s.). The mobile phase consisted of acetonitrile and phosphate buffer pH 4.0 in the ratio 60 : 40. The flow rate and injection volume were 1.0 mL/min and 15 μL, respectively. The peaks were monitored at 272 nm. The average retention time is 5.136 min. The linearity of the method was investigated in the range of 10–50 μg/mL and r2 was found to be larger than 0.9987. The LOD and LOQ were found to be 1.853 and 5.615 μg/mL, respectively. Results indicated that the degradants are well resolved and separated from the prodrug. Hydrolysis kinetics studies were carried out in buffer solutions (pH 1.2, 5.5 and 7.4) to establish the fate of the prodrug. The half-lives in the respective buffers were 23.5, 262, and 334 hours indicating sufficient stability to attain the goal of oral delivery.